Prevalence of Different Spinal Cord Injuries After Trauma and Its Comparison With the ASIA Scale - Silvia, Sana; Khan, Atiq Ahmed; Khursai, Muhammad Sameer; Shah, Irfan Ali; Shahnawaz, Shahida; Ayeshah, Shabih (Biological and Clinical Sciences Research Journal, 2025)
Traumatic spinal cord injury (SCI) is a major cause of disability, particularly in low- and middle-income countries, where road traffic accidents and falls are common contributors. Early identification of injury patterns on magnetic resonance imaging (MRI) and their correlation with neurological grading systems such as the American Spinal Injury Association (ASIA) scale may provide prognostic value. However, limited data are available from Pakistan regarding MRI-defined SCI types and their relationship with neurological impairment. Objective: To determine the prevalence of MRI-defined traumatic spinal cord injury (SCI) types (cord contusion, oedema, haemorrhage) among adults presenting to SMBBIT, DUHS, Karachi, and to compare these with ASIA impairment grades at presentation. Methods: A six-month, cross-sectional study employed non-probability sampling conducted from 1st September 2024 to 28th February 2025. Adults (18–60 years) with traumatic SCI presenting within two months of injury were included; non-traumatic cord dysfunctions were excluded. Demographics, injury characteristics, and ASIA grades (A–E) were recorded. MRI categorised SCI as cord contusion, oedema, or haemorrhage. Quantitative variables were summarized as the mean ± SD; qualitative variables were summarized as n (%). Associations between SCI type and ASIA grade, as well as effect modification by age group, gender, mechanism, and injury duration, were assessed using chi-square tests (α = 0.05). Results: Eighty-three patients were analysed (mean age 37.77±10.15 years; 72% male; 74% urban). Mean height, weight, BMI, and injury-to-presentation interval were 1.71±0.09 m, 71.63±14.60 kg, 24.4±4.3 kg/m², and 32.46±18 days, respectively. Road traffic accidents predominated (59%), followed by falls from heights (23%), assaults (11%), and other incidents (7%). ASIA distributions were as follows: C-Incomplete (35%), D-Incomplete (22%), A-Complete (22%), B-Incomplete (18%), and E-Normal (4%). The MRI patterns were as follows: cord contusion (58%), cord oedema (23%), and cord haemorrhage (19%). The SCI type–ASIA association was not statistically significant (χ², P=0.298). Stratified analyses revealed no significant effect modification by age (P = 0.214), gender (P = 0.521), mechanism (P = 0.819), or duration (P = 0.903). Conclusion: In this young, predominantly male cohort, cord contusion was the commonest MRI pattern, and incomplete ASIA grades predominated. The SCI type did not show a significant correlation with the ASIA grade at presentation. Larger, longitudinal studies are warranted to refine prognostication and inform prevention strategies.